Blood bound - Briggs, Patricia (Briggs, Patricia. Mercy Thompson novels, 2007)
Jalopy mechanic and were-creature Mercedes Thompson can change into a coyote whenever she wants to. As a favor, she agrees to back up vampire friend Stefan when he confronts another of his kind. But, being demon-possessed, that vampire proves deadlier than most and before she can do anything to help, Mercedes is in the middle of a war with vampires and werewolves.